Investigation of Non-invasive Blood Biomarker Detection for Oral Systemic Disease - Manoj Meena; Tulsi Subramaniam; Monali R. Nikalje; Bhuvaneshwari Karthiyeyan; Arjit Vihan; Sagolshem D. Devi (Journal of Pharmacy and Bioallied Sciences)
Context: Oral systemic illnesses are associated with other systemic health issues, such as cardiovascular diseases, diabetes, and autoimmune disorders. The discovery of dependable biomarkers is crucial for the early diagnosis and monitoring of these illnesses. The identification of non-invasive blood biomarkers has emerged as a viable diagnostic method, providing improved patient compliance and reduced procedure risks. This research seeks to assess the efficacy of certain non-invasive biomarkers in the diagnosis and monitoring of oral systemic illnesses. Materials and Methods: A total of 100 individuals (50 with clinically confirmed oral systemic illnesses and 50 healthy controls) were recruited from a tertiary care facility. Non-invasive peripheral blood samples were obtained with a micro-collection device. Biomarkers such as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) were evaluated by enzyme-linked immunosorbent assay (ELISA). Statistical study used ANOVA and regression models to ascertain the relevance and association between biomarker levels and illness severity. Outcomes: The concentrations of CRP, IL-6, and TNF-α were markedly increased in patients with oral systemic illnesses compared to healthy controls (CRP: 10.2 ± 2.1 mg/L vs. 2.5 ± 0.8 mg/L, P < 0.01; IL-6: 8.7 ± 1.5 pg/mL vs. 3.2 ± 0.9 pg/mL, P < 0.01; TNF-α: 12.4 ± 2.0 pg/mL vs. 5.1 ± 1.3 pg/mL, P < 0.01). Regression analysis revealed a robust positive connection between IL-6 and illness severity (r = 0.82, P < 0.01). The sensitivity and specificity of the combined biomarker detection were 92% and 88%, respectively. Final Assessment: Non-invasive detection of blood biomarkers has considerable promise in diagnosing and managing oral systemic illnesses. Increased concentrations of CRP, IL-6, and TNF-α are dependable markers of illness existence and intensity.